Neurologic Complications of Acute Posterior Multifocal Placoid Pigment Epitheliopathy: A Case Series of 4 Patients. (July 2018) - Tsuboyama, Melissa; Chandler, Justin V.; Scharf, Eugene; Scagnelli, John; Ramchandran, Rajeev S.; Holloway, Robert; Wychowski, Thomas
Acute posterior multifocal placoid pigment epitheliopathy (APMPPE) is a self-limited idiopathic inflammatory ophthalmologic condition with characteristic funduscopic and fluorescein angiography findings. It is typically characterized by a flu-like prodrome followed by monocular or binocular vision loss. Often, prognosis is excellent with complete or near-complete recovery of vision. Rarely, however, APMPPE is associated with neurologic complications, including meningitis, cerebral vasculitis, and stroke. Treatment in patients with central nervous system (CNS) involvement involves steroids and ultimately other immunosuppressive therapy, as there can be significant resulting morbidity and mortality otherwise. Evidence or guidelines regarding duration of treatment are lacking. We present 4 patients diagnosed with APMPPE who demonstrate the spectrum of neurologic sequelae associated with APMPPE. The first 2 cases highlight cerebrospinal fluid lymphocytic pleocytosis as an indicator of active CNS inflammation and the potential utility of serial lumbar punctures (LPs) to guide treatment duration. Cases 3 and 4 demonstrate the neurovascular complications seen in CNS vasculitis. Case 4 also highlights the potential use of magnetic resonance vessel wall imaging (VWI) as a noninvasive means for disease surveillance and treatment guidance. This case series emphasizes the importance of recognition by neurologists of APMPPE as an entity associated with strokes and cerebral vasculitis in order to provide appropriate and timely treatment. Active CNS inflammation warrants continued aggressive immunosuppressant treatment, and we propose that serial LPs and/or magnetic resonance VWIs may be effective tools to guide disease surveillance and subsequent treatment duration.